Lesões intra-epiteliais e câncer do colo do útero em índias do estado do Maranhão - MELO, Cristiane Dominice (2012)
Cancer of the cervix is the second type of cancer that affects most women and is considered a serious public health problem. The main risk factor for this disease is related to the human papillomavirus, which is associated with other factors have accelerated their infection leading, thus the development of cancer The ignorance about basic health issues of indigenous women, in which the paucity of investigations and the absence of census and other regular surveys, allied precariousness of information systems, make it impossible to trace satisfactorily the epidemiological profile of this population in Brazil. This is a cross sectional descriptive study aimed to assess the prevalence of cellular changes in cervical smears of indians women of the state of Maranhão in 2011 assisted by FUNASA-MA. Were collected 805 samples of cervicovaginal secretions of indigenous women, whose clinical data were obtained by applying specific questionnaire. The median age was 31 years, ranging from 13 to 75 years. 6,4% were obtained positivity distributed in 21% of ASC-US, 10% ASC-H, LSIL 38%, 27% and 4% of HSIL of squamous cell carcinoma. The distribution of cellular changes by age group showed greater evidence of atypia in the age groups 21 to 30 years with 34,62%, with the highest percentage being LSIL lesions 61,1%. In the age groups 12-20 years and 31-40 years, obtained a percentage of 23,08% of atypias, and the ASC-US more prevalent in the range of 12 to 20 years with 41,6% and HSIL with the highest percentage 58,3% of injuries in the range of 31 to 40 years The most commonly identified infectious etiology was bacterial vaginosis. This study demonstrated a wide variation in the fertility rate, and the median was 3 children. In univariate analysis was evident as risk factors for positive diagnosis of cellular alteration the habit of having multiple partners, smoking, and be performing the first collection. It can be concluded that the Pap smear is an excellent method to trace lesions precursor cancer. However, it is necessary to increase the coverage and systematic examination for the Indian women are better assisted to effective prevention.